How Public Investment Could Help Strengthen Iran's Growth Potential : Issues and Options - Sadeghi, Amir (IMF Working Papers; Working Paper, 2018)
Public investment is key to growth in developing oil-exporting countries and oil revenue is an important source of finance for public investment. Assessing the growth impact of public investment in Iran under various investment scaling-up (gradual, aggressive, and conservative) and oil price (baseline and adverse) scenarios, this paper shows that because of absorptive capacity constraint and investment inefficiency the growth outcome of an aggressive investment scaling-up is not significantly different from a conservative or a gradual scenario while its costs, in terms of fiscal adjustment, are significantly higher, especially during low oil price periods. An improvement in investment efficiency has a significant positive impact on growth outcome and leads to higher private consumption and investment. Using an oil fund, on the other hand, can help contain the size of fiscal adjustments, although it would result in a larger appreciation of real exchange rate and deterioration in the current account balance.